PENINGKATAN DAYA SAING EKONOMI INDONESIA - FX Sugiyanto (Jurnal Dinamika Ekonomi & Bisnis, 2004)
Competitiveness is a key factor in a global market. Not only firms have to raise their competitiveness, but also nations. Therefore competitiveness can be seen both in the micro and macro perspective. In the macro perspective, the ability of those nations to create employment and raise productivity of their resources represent the competitiveness of nations. While in the micro perspective, competitiveness of a firm is represented by a relative cost comparative. Firms have to generate efficien cost in their production to raise their competitiveness. There are a lot of attributes determine competitiveness; resources, domestic demand, related industries, strategy, structure and competitive conditions in domestic market. Among ASEAN countries, the competitiveness of Indonesia is the weaker It is important for Indonesia to conduct some policies to enforce all those attributes determining competitiveness in the more liberalized economy.